Gendun Chopel: Tibet's modern visionary - Lopez, Donald S., Jr. (Lives of the masters, 2018)
"The most comprehensive work available on the life and writings of Tibet's most famous modern cultural hero. Poet, prolific writer, Buddhist philosopher, adventurer, madman, and saint can all be used to describe Gendun Chopel (1903-1951). The life and writings of this cultural prophet of the Himalayas represent a key turning point in Tibetan religious and cultural history, when twentieth-century modernity came crashing into Tibet as a result of the Great Game and the invasion of Communist China. Gendun Chopel was a recognized reincarnation (tulku), a Gelukpa monk, and a nonsectarian Buddhist practitioner. He eventually became Tibet's first modern artist and writer, largely due to his extensive time abroad and exposure to Western culture in British India. Gendun Chopel was little appreciated in his lifetime, though he was known by the Tibetan elite for his scholarship and progressivist ideas, which eventually landed him in a Lhasa prison. While he did not accrue many followers in his lifetime, his love of the Dharma and extensive contributions to Tibetan Buddhist philsophy count him among the greatest Buddhist masters to have come from Tibet.No contemporary scholar knows Gendun Chopel better than Donald S. Lopez, Jr., who has written six books on the figure so far. Lopez intimately and eloquently carries the reader through the life of Gendun Chopel, setting the stage for his selected writings, which present the range and depth of Chopel's thought"--